Frequencies of interleukin-6, GST and progesterone receptor gene polymorphisms in postmenopausal women with low bone mineral density - Moura, Katia Franco; Haidar, Mauro; Bonduki, Claúdio; Feldner Júnior, Paulo Cezar; Silva, Ismael; Soares Júnior, José Maria; Girão, Manoel João (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Osteoporosis is a skeletal disorder characterized by low bone mineral density (BMD). Studies have shown that some of the genetic components relating to lower BMD may be detected by polymorphisms. Our aim was to evaluate the frequencies of interleukin-6, GST and progesterone receptor gene polymorphisms in postmenopausal women with low BMD. DESIGN AND SETTING: Cross-sectional study, conducted in a public university in São Paulo, Brazil. METHODS: We evaluated interleukin-6 (IL-6), progesterone receptor gene (PROGINS) and glutathione S-transferase (GST) polymorphisms in 110 postmenopausal women with no previous use of hormone therapy. Tests were performed using DNA-PCR, from oral scrapings. We used Student’s t-test and a logistic regression model for statistical analysis. RESULTS: Regarding IL-6 polymorphism, 58.2% of the patients were homozygotes (GG) and 41.8% had allele C (heterozygote or mutant homozygote + GC or CC). PROGINS genotype polymorphism was absent in 79% (wild homozygote or P1/P1) and present in 20.9% (heterozygote or P1/P2). Regarding GSTM1 polymorphism, the allele (1/1) was present in 72.7% of the patients and was absent in 27.3%. We found that IL-6 polymorphism had statistically significant correlations with the L2-L4 T-score (P = 0.032) and with BMD (P = 0.005). Women with IL-6 polymorphism were 2.3 times more likely to have a L2-L4 T-score of less than -1, compared with those not presenting this polymorphism. CONCLUSION: IL-6 gene polymorphism was correlated with low BMD, whereas the PROGINS and GSTM1 polymorphisms did not show any correlation.